2017
DOI: 10.1089/end.2017.0490
|View full text |Cite
|
Sign up to set email alerts
|

Retzius-Sparing Robotic-Assisted Laparoscopic Radical Prostatectomy: A Safe Surgical Technique with Superior Continence Outcomes

Abstract: Retzius-sparing RALP requires shorter console time, is oncologically safe, and leads to significantly superior continence outcomes compared with conventional RALP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 15 publications
4
73
1
Order By: Relevance
“…This superiority might be maintained or equalized at 1 year . A few studies have compared the early oncological results between RS‐RARP and standard RARP and no significant difference was found . Recently, our group reported the mid‐term oncological outcomes of patients with high‐risk PCa treated with RS‐RARP and these were similar to those of large studies of conventional RARP.…”
Section: Summary Of Early Oncological Outcomes Of Retzius‐sparing Robsupporting
confidence: 57%
See 3 more Smart Citations
“…This superiority might be maintained or equalized at 1 year . A few studies have compared the early oncological results between RS‐RARP and standard RARP and no significant difference was found . Recently, our group reported the mid‐term oncological outcomes of patients with high‐risk PCa treated with RS‐RARP and these were similar to those of large studies of conventional RARP.…”
Section: Summary Of Early Oncological Outcomes Of Retzius‐sparing Robsupporting
confidence: 57%
“…found that the higher continence rate at 1 week (73.3% RS‐RARP vs 26.7% standard RARP; P = 0.000) had vanished at 1 year (100% vs 93.3%; P = 0.15). By contrast, a large recent prospective series showed that the superiority of RS‐RARP in terms of higher early urinary continence was maintained at 1 year (97.5% RS‐RARP vs 68.5% standard RARP) .…”
Section: Summary Of Early Oncological Outcomes Of Retzius‐sparing Robmentioning
confidence: 86%
See 2 more Smart Citations
“…The answers to all of these questions cannot be fully answered yet, but several trends are apparent from the results of existing series ( Table 1). [2][3][4][5][6] Advantages of RS-RARP Early (one to four weeks after surgery) pad-free rates appear to be consistently lower after RS-than AA-RARP ( Table 1). Given that post-prostatectomy stress urinary incontinence (PPSUI) has the greatest single influence 7 of all the various consequences of radical prostatectomy (RP) that negatively impact a patient's quality of life, 8 this is of considerable importance.…”
mentioning
confidence: 99%